Coupling and Coordinated Development Evaluation of Society-Ecology-Water Resources System in Central Yunnan - HE Guilin; ZHANG Daiqing; CHENG Guaimei; GENG Yiqiao; LI Haokun (Renmin Zhujiang)
Exploring the coupling and coordination relationship among society, ecology, and water resources in central Yunnan is of significance to the sustainable development of central Yunnan and Yunnan.Based on emergy analysis and dual water resources sustainable development theory, this paper constructs the emergy evaluation index system of the regional social-ecological-water resources system and employs the coupling coordination degree model to explore the system development index and coupling coordination degree of central Yunnan from 2006 to 2020.The results show that in the past 15 years, the socio-economic development of central Yunnan has developed rapidly, the development of water resources and ecological environment has lagged, and the coupling degree is higher than the coordination degree.Additionally, the coupling coordination degree shows an overall positive development trend, and most areas are above grade IV.In 2006, the spatial distribution of coupling coordination degree showed a trend of a high degree in the north and a low degree in the south.Liuzhou City in the north and Honghe River in the south were in the primary and barely coupled and coordinated development stage respectively.In 2015, there was a trend of high degree in the west and low degree in the east, which all reached the primary coordinated development stage and above, and Lijiang changed greatly to the intermediate coupling coordinated development stage.In 2020, the tendency presented a high degree in the middle and a low degree in the areas around.Lijiang was still in the leading position in the intermediate coupling and coordinated development stage, and the rest of the cities were in the primary coupling and coordinated development stage.